2014
DOI: 10.1108/mf-07-2013-0182
|View full text |Cite
|
Sign up to set email alerts
|

Testing the monthly anomaly with stochastic dominance

Abstract: Purpose – This study uses stochastic dominance (SD) theory to examine whether the traditional festival, such as the Spring Festival (often in February), affects the patterns of monthly anomaly for the Taiwan Stock Exchange (TWSE). The paper aims to discuss these issues. Design/methodology/approach – The authors employ a new bootstrap-based test due to Linton, Maasoumi and Whang (hereafter LMW). The LMW test is well suited for financial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…However, the study detected the September effect consistently throughout the study period in all the estimations of return series. This present study supports the study of Ciccone and Etebari (2008), Ke et al (2014) and Bajaj et al (2019). The September effect as detected in the study has several plausible explanations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the study detected the September effect consistently throughout the study period in all the estimations of return series. This present study supports the study of Ciccone and Etebari (2008), Ke et al (2014) and Bajaj et al (2019). The September effect as detected in the study has several plausible explanations.…”
Section: Discussionsupporting
confidence: 93%
“…However, Floros (2008) reported the significance of June and October in the Greece stock market. Analysing for the period 1980–2009, Ke et al (2014) found the February effect in the Taiwan stock exchange. Similarly, Munir and Ching (2018) disclosed the presence of month effect on the share value of the selected banking and non-banking companies in Malaysia.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Returns in the holy month of Ramadan (the festival of Muslims) 98 JAMR 15,1 being higher that the rest of the months has also been documented before by Al-Hajieh et al (2011) and Bialkowski et al (2013). Ke et al (2014) had documented the Spring Festival effect. On the similar lines, Sakakibara et al (2013) had reported "Dekansho-bushi" effect.…”
Section: Cultural Factors (Diwali Effect)mentioning
confidence: 92%
“…The method has been widely used in prior financial research on such topics as the IPO effect (Abhyankar et al 2006), the Monday effect (Cho et al 2007), the yen carry trades (Fong 2010), the monthly effect (Lee et al 2013;Ke et al 2014), the value premium (Hsu et al 2015), and the dim sum bond (Fung et al 2014). The stochastic dominance method offers several advantages (Linton et al 2005;Abhyankar et al 2006).…”
Section: Introductionmentioning
confidence: 98%